Fast MR arthrography of the shoulder joint using VIBE to evaluate the rotator cuff - Vandevenne, J. E.; Vanhoenacker, F. M.; Gelin, G.; Velghe, B.; Palmers, Y.; de Schepper, A.; Parizel, P. M. (Medicine and Science in Tennis, 2007)
Concerning the radiologist dealing with tennis players, the demand is high for immediate and accurate diagnosis after a shoulder joint injury. Until recently, diagnostic imaging in the acute phase after injury mostly relied on radiography and ultrasound examinations. Ultrasonography is readily available and cheap, but has its limitations because the accuracy is operator-dependent and ultrasonography does not show all shoulder joint structures. In recent years, both professional and recreational tennis players are increasingly seeking magnetic resonance (MR) imaging soon after trauma. MR arthrography (MRA) is a well established and accurate imaging modality for diagnosis of internal derangements of the shoulder joint. However, immediately following trauma patients are often in pain during the MR examination and can only be immobilised for a short time. Applying the standard MR sequences, mainly spin echo T1-weighted fast saturated (T1-FS) with acquisition times of 5 mins for each imaging plane, often results in degraded MR images due to movement artefacts.